PHENOMENCES OF VIOLENCE ON THE NAME OF RELIGION TOWARDS TERRORISM ACTS - Willy Willy; Billy Samuel Karwur; Yoas Wicaksana Karouw (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Abstract This research originated from the existence of violence in the name of religion, namely the religion of Islam, such as destroying buildings, brutal actions, and destroying property. This is due to the impact of religious freedom which gave birth to many different ideologies, one of which is violence in the name of religion with the aim of amar ma'ruf nahi mugkar or an order to invite good and prevent bad but with violence. In the criminal law, there are criminal acts against religion, namely article 156a of the Criminal Code which regulates criminal acts of religious enmity, abuse and blasphemy. The word abuse of religion has a very broad meaning, as well as the ambiguity of the word abuse, this causes legal certainty not to be achieved. This study looks at the misuse of religion as non-criminal, namely acts of violence in the name of religion by looking at the Islamic teachings on violence in the name of religion because the abuse of religion can be seen from the teachings of religion itself. This research is a normative juridical study using a statutory approach. The urgency of this research is to know and analyze the application of Article 156a of the Criminal Code in violence in the name of religion.